Search in Networks: The Case of Board Interlocks - Mitri Kitti; Matti Pihlava; Hannu Salonen (Aboa Centre for Economics (ACE), 2016)
We present a model for the dynamics of networks in which edges represent positions in organizations, holders of which are connected to each other when the positions belong to the same organization. Once a vacancy is opened, the new employee can be hired from the current network. In particular, it is possible that the further away a candidate is in the network from the firm having the vacant position, the less likely it is that the candidate is chosen. The search may also involve preferential attachment in the sense that people with high numbers of positions are more likely to be chosen. Microeconomic foundations of the search process are presented. An empirical application to a board interlock network demonstrates that the model is capable of explaining how such networks are formed. It is observed that distances from firms to candidates and the candidates' numbers of positions drive the process.
Keywords: D83; D85; Z13; 330; search; two-mode network; network formation; board interlock network